2023
DOI: 10.3390/foods12030586
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Poly(L-Lactic Acid)-Based Soft Films with Gas Permselectivity for White Mushrooms (Agaricus bisporus) Preservation

Abstract: Proper packaging can extend the shelf life and maintain the quality of mushrooms during storage. The purpose of this study is to investigate the preservation of Agaricus bisporus using copolymer-modified poly (L-lactide-co-butylene fumarate) and poly (L-lactide-co-glycolic acid) (PLBF and PLGA) packaging. Shelf life and quality were evaluated over 15 days of storage of Agaricus bisporus at 4 ± 1 °C and 90% relative humidity, including weight loss, browning index (BI), total phenolics (TP), ascorbic acid (AA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Since fresh-cut edible fungi contain many nutritional ingredients such as vitamins, minerals, and bio-active compounds, they have become extremely popular among consumers [ 9 ]. Generally, the shelf life of an edible fungus under normal temperature is 1–3 days [ 10 ]. Following cutting, the shelf life decreases due to increased respiration rates, which may result in the consumption of nutrient substances.…”
Section: Introductionmentioning
confidence: 99%
“…Since fresh-cut edible fungi contain many nutritional ingredients such as vitamins, minerals, and bio-active compounds, they have become extremely popular among consumers [ 9 ]. Generally, the shelf life of an edible fungus under normal temperature is 1–3 days [ 10 ]. Following cutting, the shelf life decreases due to increased respiration rates, which may result in the consumption of nutrient substances.…”
Section: Introductionmentioning
confidence: 99%
“…Referencing the process introduced by Sun et al [ 21 ], weight loss rate was calculated with the gravimetric method as follows: where m is the initial fresh weight of the T. fuciformis (in grams), and m 1 is the fresh weight of the T. fuciformis at the time of sampling (in grams).…”
Section: Methodsmentioning
confidence: 99%
“…Referencing the process introduced by Sun et al [21], weight loss rate was calculated with the gravimetric method as follows:…”
Section: Determination Of Weight Loss Ratementioning
confidence: 99%
“…The packaged meat fillets were effectively preserved for 7 days in PLA, showing values of food quality and safety in the range of commercial high-barrier multilayers, which are currently based on structures made of non-biodegradable polymers that are extremely difficult to recycle. Finally, Sun et al [10] demonstrated that films of poly(L-lactide-co-butylene fumarate) (PLBF) and poly(L-lactide-co-glycolic acid) (PLGA) can successfully extend the shelf life and maintain the quality during cold storage of white mushrooms (Agaricus bisporus). These copolymers have the advantage to modify the oxygen (O 2 ) and carbon dioxide (CO 2 ) ratio of PLA, resulting in lower permeability values.…”
mentioning
confidence: 99%